Analysis Of The Determinants Of Pt Dua Putra Employee Performance Utama Makmur Tbk Pati Through Employee Welfare: ANALISIS DETERMINAN KINERJA KARYAWAN PT DUA PUTRA UTAMA MAKMUR TBK PATI MELALUI KESEJAHTERAAN KARYAWAN - Widiani Ayu Lestari,; Efriyani Sumastuti,; M. Fadjar Darmaputra, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to understand and analyze the effect of salary, allowances, and job promotion on employee performance with employee welfare as an intervening variable. The population of this study were all employees working at PT Dua Putra Utama Makmur Tbk Pati. The research method used is a quantitative research method with a descriptive approach. The sampling method used is a saturated sample, with a total of 100 employees as respondents with the SmartPLS version 3.0 statistical analysis technique.The results of this study show that Salary does not have a positive effect on employee welfare, Salary has a positive effect on employee performance, Allowances have a positive effect on employee welfare, Allowances have a positive effect on employee performance, Position promotion has a positive effect on employee welfare, and Employee welfare has a positive effect on employee performance, In addition, Salary has a positive effect on employee performance through mediation employee welfare on, Allowances have a positive effect on employee performance through employee welfare mediation, and Position promotion has a positive effect on employee performance through employee welfare mediation.